To find the remainder when f(x) = x^4 - 3x^3 + 7x - 1 is divided by (x-2), we can use synthetic division.
We set up the division with 2 as the divisor:
2 | 1 -3 7 -1
-----------------------
2 -2 10 19
The remainder is the last value in the bottom row, which is 19.
Therefore, the remainder when f(x) is divided by (x-2) is 19.
To determine if (x-4) is a factor of f(x) = x^5 - 3x^4 - x - 3, we can use the factor theorem.
The factor theorem states that if (x-a) is a factor of f(x), then f(a) = 0.
To use this theorem, we substitute the value of a = 4 into f(x) and check if f(4) = 0.
f(4) = (4)^5 - 3(4)^4 - (4) - 3
= 1024 - 3(256) - 4 - 3
= 1024 - 768 - 7
= 249
Since f(4) is not equal to 0, (x-4) is not a factor of f(x).
Therefore, the answer is D. (x-4) is not a factor because f(4)≠0.
what is the remainder when the function
f(x)=x^4-3x^3+7x-1 is divided by (x-2)
A. 2
B. 5
C. 17
D. 25
Use the factor theorem to determine if (x-4) is a factor of x^5-3x^4-x-3
A. (x-4) is a factor because f(4)=0
B. (x-4) is a factor because f(4)≠0
C. (x-4) is not a factor because f(4)=0
D. (x-4) is not a factor because f(4)≠0
1 answer